The essential guide to doing your research project - O'Leary, Zina.; O'Leary, Zina. (Los Angeles : Sage, 2010)
This is a comprehensive, practical and engaging guide to understanding and embarking upon social science research. By adopting a clear and accessible approach, the text encourages students to think about, and engage with, every aspect of the research process.
Taking the leap into the research world -- Getting started -- Striving for integrity in the research process -- Developing your research question -- Crafting a research proposal -- Working with literature -- Designing a research plan -- Understanding methodologies: quantitative, qualitative, and 'mixed' approaches -- Understanding methodologies: evaluative, action-oriented, and emancipatory strategies -- Seeking 'respondents' -- Direct data collection: surveys and interviews -- Indirect data collection: working with observations and existing text -- Analysing quantitative data -- Analysing qualitative data -- The challenge of writing up.
1st published 2004 as: Essential guide to doing research.
Keywords: Research